1996
DOI: 10.1073/pnas.93.8.3259
|View full text |Cite
|
Sign up to set email alerts
|

The brain-specific activator p35 allows Cdk5 to escape inhibition by p27Kip1 in neurons.

Abstract: Cell cycle withdrawal in postmitotic cells involves cyclin-dependent kinase (Cdk)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 34 publications
8
88
0
Order By: Relevance
“…Moreover, overexpression of p27 kip1 alone is sufficient to induce neuronal differentiation in a mouse neuroblastoma cell line (52). The kinase activity of p35⅐Cdk5, however, is not inhibited by p21 cip1/WAF1 or p27 kip1 (33,34). We also found that the activity of bacterially expressed p25⅐Cdk5 is not inhibited by recombinant p21 cip1/WAF1 or p27 kip1 .…”
Section: Discussionsupporting
confidence: 50%
“…Moreover, overexpression of p27 kip1 alone is sufficient to induce neuronal differentiation in a mouse neuroblastoma cell line (52). The kinase activity of p35⅐Cdk5, however, is not inhibited by p21 cip1/WAF1 or p27 kip1 (33,34). We also found that the activity of bacterially expressed p25⅐Cdk5 is not inhibited by recombinant p21 cip1/WAF1 or p27 kip1 .…”
Section: Discussionsupporting
confidence: 50%
“…One possibility is that association of cyclin D2 with cdk-5 enables the Cip/Kip family of cdk inhibitors (for reviews, see Lees, 1995;Pines, 1995;Sherr and Roberts, 1995) to bind to cdk-5 and abolish cdk-5 activity, whereas association of p35 with cdk-5 is refractory to Cip/Kip binding. Indeed, it has recently been demonstrated that one Cip/Kip inhibitor that is highly expressed in postmitotic neurones, p27 KipI binds in vitro to cdk-5/cyclin D2 complexes but not to cdk-5/p35 complexes (Lee et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recent works offer insights into the molecular mechanisms by which ATRA exerts its biological effects on neuroblastomas. All-trans-retinoic acid activates phosphatidylinositol 3 0 -kinase-Akt pathway that plays an important role in neuronal differentiation (Encinas et al, 1999;Lopez-Carballo et al, 2002), and it reduces the expression levels of MYCN (Thiele et al, 1985) and upregulates the cyclin-dependent kinase (CDK) inhibitor p27 KIP1 in association with the ATRA-induced cell cycle arrest in neuroblastoma cells (Lee et al, 1996;Nakamura et al, 2003). In addition, certain neuroblastoma cells underwent apoptosis in response to ATRA (Piacentini et al, 1992;Takada et al, 2001;Nagai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%